2003
DOI: 10.1124/jpet.103.054155
|View full text |Cite
|
Sign up to set email alerts
|

Functional Analysis of Three Genetic Polymorphisms in the Glucocorticoid Receptor Gene

Abstract: Glucocorticoids are widely used as potent anti-inflammatory drugs. Glucocorticoids exert their pharmacological effects by binding to a glucocorticoid receptor (GR), which promotes expression of its target genes or suppresses transcription mediated by other transcriptional factors, such as nuclear factor-B (NF-B). To identify genetic polymorphisms affecting glucocorticoid responses, the GR gene was sequenced, and two novel single nucleotide alterations, 1510AϾT (T504S) and 1952CϾT (S651F), were identified in ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 30 publications
2
11
0
Order By: Relevance
“…However, it was reported that hPXR ligands induced the enhanced binding of coactivators, such as steroid receptor coactivator-1, resulting in transactivation of the CYP3A4 promoter/enhancer consisting of PXR-responsive element and XREM Honkakoski and Negishi, 2000). Thus, our data support that hPXR ligands, such as rifampicin, promote the activation of nuclear hPXR rather than the translocation of the receptor to the nucleus, in contrast to the cases of VDR and glucocorticoid receptor (Racz and Barsony, 1999;Koyano et al, 2003).…”
Section: Discussionsupporting
confidence: 75%
“…However, it was reported that hPXR ligands induced the enhanced binding of coactivators, such as steroid receptor coactivator-1, resulting in transactivation of the CYP3A4 promoter/enhancer consisting of PXR-responsive element and XREM Honkakoski and Negishi, 2000). Thus, our data support that hPXR ligands, such as rifampicin, promote the activation of nuclear hPXR rather than the translocation of the receptor to the nucleus, in contrast to the cases of VDR and glucocorticoid receptor (Racz and Barsony, 1999;Koyano et al, 2003).…”
Section: Discussionsupporting
confidence: 75%
“…Glucocorticoids bind to a cytoplasmic receptor, the glucocorticoid receptor, which moves to the nucleus and activates steroid-responsive genes containing the glucocorticoid response element (GRE). Several polymorphisms have been described in the glucocorticoid receptor (GR) gene with functional consequences-for example, a Val641Asp polymorphism influences the binding affinity for dexamethasone [39], a Val729Ile polymorphism confers a fourfold decrease in dexamethasone activity [40], an Asn363Ser polymorphism was associated with higher sensitivity to dexamethasone [41], and 2314insA and S651F variants had a suppressed glucocorticoid receptor messenger RNA and protein levels in a recombinant system [42]. These data demonstrate that multiple polymorphisms exist in the glucocorticoid receptor; however, several of the polymorphisms are rare, and their functional significance is questionable [4].…”
Section: Pharmacogenetics Of Glucocorticoid Therapymentioning
confidence: 99%
“…HeLa cells (2.8 ϫ 10 4 cells) were cotransfected with 100 ng of the wild-type hAhR expression plasmid pcDNA 3.2-DEST hAhR or the variant hAhR expression plasmid together with 100 ng of the hArnt expression plasmid, 30 ng of pGL3-hCYP1A1 promoter plasmid, and 10 ng of phRL-TK plasmid as an internal control. Four hours after transfection, the cells were treated with a vehicle (DMSO) or various concentrations of BNF, 3MC, or OME, and then cultured for an additional 48 h. The cells were washed with PBS, and the lysates were prepared using the dual luciferase reporter assay system (Promega) described previously (Koyano et al, 2003. All transfection efficiencies were normalized according to the Renilla luciferase activity.…”
Section: Methodsmentioning
confidence: 99%
“…Immunocytochemistry was performed as described previously (Ikuta et al, 1998;Koyano et al, 2003). Briefly, HeLa cells (1.4 ϫ 10 5 cells) were transfected with 600 ng of the expression plasmid for empty, wild-type, or variant AhR together with 600 ng of the Arnt expression plasmid, and then cultured for 4 h. The cells were treated with a vehicle (DMSO) or 1 M 3MC for 48 h. Transfected HeLa cells were washed twice with PBS, fixed with 3.7% formaldehyde in PBS for 15 min at room temperature, and then permeabilized with 0.5% Triton X-100 for 15 min.…”
Section: Functional Analysis Of Human Ahr Variantsmentioning
confidence: 99%